An Anatomical Dissection Method for Observation of Fibrous Facial Structures. Issue 3 (22nd November 2022) - Hashiguchi, Shin-ichiro; Hayakawa, Koji; Inoue, Eiko; Han, Aya; Iwanaga, Joe; Tabira, Yoko; Yamashita, Akihiro; Rikimaru, Hideaki; Kiyokawa, Kensuke; Watanabe, Koichi
Abstract : Background: In recent years, structures including the superficial musculoaponeurotic system and retaining ligaments that support the facial soft tissue have been clarified. However, these structures are very difficult to observe in their entirety by the standard gross anatomical procedure (ie, dissection from superficial to deep layers). Furthermore, accurate descriptions of these structures are rare in both anatomical and plastic surgery textbooks. The aim of this study was to clarify the facial fibrous structures in a gross anatomical view. Methods: The authors' novel method used soft facial tissue and bone. The tissue was fixed in gelatin and sectioned at a thickness of 5 to 10 mm. Each section was placed on a wooden board; the bone was then pinned, and the skin was pulled outward with sutures to hyperextend the soft tissue. Subsequently, the loose connective tissue was torn and fat tissue was removed under a surgical microscope. After the removal of fat tissue, the fibrous facial structures (eg, the superficial musculoaponeurotic system and retaining ligaments) could be observed clearly. Results: The thickness of the sections allowed three-dimensional observation, such that a structure located deep within a section could be clearly observed. The expansion of soft tissue facilitated observation of the facial layer and fibrous structures, and the locations of nerves and vessels. Therefore, the facial layer structure was readily discerned. Conclusion: This method is likely to be very useful in the field of plastic surgery because it enabled intuitive identification of facial layers and their characteristics. Clinical Relevance Statement: The dissection method developed by the authors reveals the connected morphology of each tissue of the face, thus providing basic data for analyzing soft tissue changes due to aging and gravity. This will be useful for the development of anti-aging medicine.